First lactation production traits of Frieswal cows under field conditions (Indian Journal of Animal Production and Management, 2018)
The Frieswal (HFxSahiwal crossbred) cows are important for milk production in India. An investigation  was carried out with farmers of U.S.Nagar district of Uttarakhand on Frieswal cows (Nov. 2010 to Feb.  2016) to study the effect of various non-genetic factors (blocks, herd size, land holding, education level of  farmers, caretakers of herd, marketable milk surplus, season/ year of calving) on first lactation production  traits using least-squares analysis of variance. The overall values for lactation length and 305-days milk  yield based on 220 observations were 11.32±0.65 kg, 342.97±12.14 days, 2434.72±187.12 kg; and of  monthly fat test for 2nd, 5th and 8th month and overall fat test based on 236 observations were 3.447±0.073,  3.735±0.075, 3.908±0.075 and 3.694±0.061 per cent, respectively. These traits were significantly affected  by varying non-genetic factors. Information on this aspect may be useful while implementing field based  animal breeding program of crossbred cattle.
Keywords: First lactation; Frieswal cattle; Production traits